Development of a Tetraplex Digital PCR Assay for the Detection of Invasive Snake Species in Florida, USA - Melissa A. Miller; Melody Bloch; Sergio A. Balaguera‐Reina; Kevin A. Olejniczak; Cynthia A. Fussell Persaud; Ericka E. Helmick; Frank J. Mazzotti; Brian W. Bahder (Ecology and Evolution)
ABSTRACT Florida, USA is a hotspot of biological invasions with over 500 non‐native species reported. Reptiles encompass most of the non‐native wildlife with over 50 species established, many of which are sympatric and are identified as invasive due to their impacts to the environment, economy, and human health and safety. Reports of new non‐native reptiles occur, and many established non‐native reptiles continue to expand their ranges in Florida, increasing the need for multitaxa detection and monitoring capabilities. Invasive constrictor snakes are a primary focus of management efforts due to life history traits that favor successful establishment and dispersal in Florida as well as their impacts to native wildlife and Everglades restoration efforts. While traditional survey methods that rely on visual detections fail to reliably detect invasive constrictors, environmental DNA (eDNA) has proven to be a promising method for detection of cryptic and rare species across the landscape. To address emerging needs for multispecies detection and monitoring in Florida, we developed the first tetraplex dPCR assay designed for detection of four species of invasive constrictor snakes, including Burmese pythons (Python bivittatus), northern African pythons (P. sebae), boa constrictors (Boa constrictor), and rainbow boas (Epicrates cenchria). In this tetraplex assay, no cross‐amplification across species was documented. This assay serves as a valuable tool for faster and more accurate monitoring efforts of these invasive species in South Florida. Additionally, eDNA samples comprised of soil and water both tested positive for Burmese python DNA under controlled and semicontrolled conditions with DNA being detectable up to 2‐weeks post removal in soil samples. Water samples yielded positive detection as quickly as 5 min after exposure to the organism. These data highlight the utility and sensitivity of this protocol for eDNA monitoring.